Input Pricing and Utilization Status for Boro Rice Cultivation: Do Farmers Benefit from Input Liberalization System? - Islam, MS; Alam, MS (The Agriculturists, 2010)
A survey based study was conducted in three districts of Bangladesh to understand the mode of input pricing, problems of timely availability of inputs and the existing input subsidy scenario of Boro rice. Applying the conventional descriptive statistics, the study revealed that there are three major modes of payment for irrigation charges prevailing all over the study areas and it varied from location to location. In Satkhira, irrigation cost appeared to be 75% higher compared to that of Bogra under power operated schemes in cash payment system. Similarly, it was much higher in Satkhira under crop sharing payment system compared to that of cash payment system. Although irrigation cost stands low (Tk.5518/ha) in case of power operated scheme but frequent load shading and low voltage were considered as the major hindrance to the timely supply of irrigation water. The price of Urea fertilizer was 44% higher in Satkhira compared to that in Bogra, probably because of both reduced supply and creation of artificial crisis. The analysis further revealed that rice farmers were very hardly aware of the government subsidy on production inputs. Deep tube- well owners commonly known as water lords were found deriving the benefits of irrigation subsidy. Inadequate monitoring on fertilizer pricing and distribution led to price distortion in almost all over the study areas.